2021
DOI: 10.1186/s13011-021-00359-w
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-ethnography of cannabis marketing on social media

Abstract: Background Since 2012, several states have legalized non-medical cannabis, and cannabis businesses have used social media as a primary form of marketing. There are concerns that social media cannabis exposure may reach underage viewers. Our objective was to identify how cannabis businesses cultivate an online presence and exert influence that may reach youth. Methods We chose a cyber-ethnographic approach to explore cannabis retailers on social med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The most popular links were to Instagram and Facebook, followed by YouTube and Twitter. These links are significant because, according to prior research, social media can have a strong influence on online shopping behaviors (e.g., Asquith, 2021;Aversa et al, 2021;Jenkins et al, 2021;Meacham et al, 2018;Trangenstein et al, 2019;Whitehill et al, 2020). In fact, one survey found that youth who engaged with cannabis promotions on social media were five times more likely to report cannabis use in the past year (Trangenstein et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most popular links were to Instagram and Facebook, followed by YouTube and Twitter. These links are significant because, according to prior research, social media can have a strong influence on online shopping behaviors (e.g., Asquith, 2021;Aversa et al, 2021;Jenkins et al, 2021;Meacham et al, 2018;Trangenstein et al, 2019;Whitehill et al, 2020). In fact, one survey found that youth who engaged with cannabis promotions on social media were five times more likely to report cannabis use in the past year (Trangenstein et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, mystery shopping has been used in a number of controversial industries, including gambling (Delfabbro & King, 2021; Malischnig et al, 2021), alcohol (Barry et al, 2021; Grube et al, 2018; Kilcommons et al, 2020; Kristina et al, 2016; Paschall et al, 2020; Schelleman-Offermans et al, 2017; Van Hoof, 2019), and tobacco (Chen et al, 2021; Feltmann et al, 2021; Lakhdar et al, 2020). In fact, across countries, Elharrar et al (2020) found that mystery shopping was one of the few effective controls for preventing tobacco sales to minors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Websites of medical cannabis companies often imply product safety and efficacy, potentially leading policy makers and the public into believing unconfirmed claims . Cannabis companies carefully design social media promotional profiles to attract customers via content focusing on cannabis normalization, and state regulations of cannabis advertising are often violated . These industry activities could contribute to changing attitudes, increased cannabis use, and CUD among some users, both within and across state boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Social media platforms are significant venues for studying emerging patterns in social issues such as cannabis legalization. The messages generated by users, producers, and suppliers have the potential to reflect trends in real-time (Darren et al 2020 ; Moreno et al 2018 ; Jenkins et al 2021 ). The social media accounts of cannabis retailers have been studied on multiple platforms including Facebook (Moreno et al 2018 ; Jenkins et al 2021 ), Instagram (Jenkins et al 2021 ), and Twitter (Cavazos-Rehg et al 2014 , Daniulaityte et al 2016 ; Lamy et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The messages generated by users, producers, and suppliers have the potential to reflect trends in real-time (Darren et al 2020 ; Moreno et al 2018 ; Jenkins et al 2021 ). The social media accounts of cannabis retailers have been studied on multiple platforms including Facebook (Moreno et al 2018 ; Jenkins et al 2021 ), Instagram (Jenkins et al 2021 ), and Twitter (Cavazos-Rehg et al 2014 , Daniulaityte et al 2016 ; Lamy et al 2016 ). Twitter, an extensively used social networking platform, offers an excellent opportunity to investigate public sentiment and perceptions on social issues including cannabis use (Darren et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%